The birth of a new reality. On the politicization of the literary field in Czechoslovakia during the 1920s controversies - Kateřina Piorecká (Slovenska Literatura)
In the newly established Czechoslovak society, writers were expected to use their works to bear witness to the ongoing transformation of the world and, as creators of collective representations, to contribute to the construction and deconstruction of identities. Soon after its founding, the Devětsil association of artists began publishing programmatic texts that defined the “new reality.” This series of statements became a sophisticated collective subversion that redefined the relationship between society and art, accumulating symbolic capital in the hands of avant-gardists (at the expense of the notables and polemicists, Gisèle Sapiro). The controversy over the newly conceived reality revealed a process of politicization of literature, which Pierre Bourdieu defined as a consequence of the assertion of artistic autonomy. The acceptance of modern society as a technical civilization, including the changes in its structure, organization of work, and communication made possible by the proliferation of machine production and reproductive methods that transformed the distribution of works of art, led to the formulation of theses for new artistic movements such as poeticism, artificialism, nadrealism, and international surrealism. However, none of these artistic gestures were free of politics and remained part of the left-leaning European avant-gardes.